Between slavery and freedom : free people of color in America from settlement to the Civil War - Winch, Julie, 1953- (African-American history series., 2014)
Between Slavery and Freedom explores one of the central ironies of racial dynamics in this nation's history from the colonial era to the end of the Civil War.